Emerging ethics in rural India - Sekhar, P.C. (2002)
This paper explores the ethical dimensions of some of the current issues engaging rural India, affecting 600 million people. It uses the evolutionary framework of Sri Aurobindo's integral yoga, and also tags on to it the rights concepts of Amartya Sen's ethics. It attempts to take a balanced view between Ambedkar's perception of the ancient Indian village as a sink of localism, a den of ignorance, narrow-mindedness and communalism, and the more common and traditional, but historically untrue, idealized view of the Vedic times. In this process it also steers clear of the pitfalls in the Marxist writings or positivist research, which has taken a wrong position that there was no rule of law and therefore no ethics as understood in modern times. It then attempts to show the more external features of perennial ethics in India, the idiom, institutions and the instruments it has nurtured, and the manner it is getting integrated with and is supportive of evolving modern values of democracy and social justice in Indian villages. - Reproduced.
Keywords: Ethics